Update on The Current Management of Drug Resistant Tuberculosis (DR-TB) - Simbolon, Rohani Lasmaria; Simatupang, Elvando Tunggul Mauliate; Yovi, Indra; Fauzi, Zarfiardy Aksa (Indonesian Journal of Tropical and Infectious Disease, 2025)
Drug-Resistant tuberculosis (DR-TB) is a global public health threat that requires a comprehensive response from all parties. DR-TB cases are often overlooked and tend to increase every year. Efforts to overcome DR-TB cases began in 2009 with the use of a molecular test, Xpert MTB/Rif, as a diagnostic tool. This has now been developed with the procurement of a molecular test with Xpert MTB/XDR. This diagnostic update also formed the basis of the latest DR-TB classification terminology by not categorizing polyresistance into the DR-TB group. This step is still not in accordance with the low success rate of DR-TB treatment in Indonesia, ranging from 45-50%. The latest DR-TB management recommendations by WHO in 2022 have implemented a 6-month treatment regimen to minimize the occurrence of treatment dropout or patient treatment non-compliance. The BPaLM/BPaL regimen is a shorter-duration oral regimen that is expected to help achieve the End TB 2015-2030 targets. Previously used short-term regimens have now been modified with Ethionamide and Linezolid variants as alternatives for DR-TB management if the BPaLM/BPaL regimen does not meet the criteria for use.